Hasse's Siroe, Thirty Years Later: A Veritable Work in Progress - Mellace Raffaele (Musicology Today)
The article aims at assessing the differences between Hasse's original setting of Metastasio's Siroe in 1733 and the composer's second setting of the same drama, exactly thirty years later, in terms of dramatic, vocal, and musical balance. The two versions will be comprehensively compared with a focus on two main issues. The first is the origin of the two settings, which goes back to two distinct versions of the libretto, originally conceived by Metastasio for Venice and Naples respectively; a different starting point which gave birth to two, largely separate dramatic projects, differentiated by a number of distinctive facets. On the other hand, special attention will be devoted to the play's characters, which, though basically the same in both settings, demonstrate remarkable differences in individual characterisation and overall balance, both as far as drama and music are concerned.